Modality and Essence in Contemporary Metaphysics - Koslicki, Kathrin (My University, 2024)
Essentialists hold that at least a certain range of entities can be meaningfully said to have natures, essences, or essential features independently of how these entities are described, conceptualized or otherwise placed with respect to our specifically human interests, purposes or activities. Modalists about essence, on the one hand, take the position that the essential truths are a subset of the necessary truths and the essential properties of entities are included among their necessary properties. Non-modalists about essence, on the other hand, oppose the reduction of essence to modality and hold, rather, that essence is more basic than, and explanatory of, modality. This chapter begins with a brief summary of Kit Fine’s well-known challenges to the modal account of essence and considers a recent attempt by “sparse modalists” like Sam Cowling and Nathan Wildman to respond to Fine’s counterexamples by adding a sparseness constraint to the “bare” modal account of essence. A further question arises, however, as to whether and how Fine’s definitional approach can avoid his own counterexamples against the modal approach to essence. The chapter concludes with some final thoughts concerning the theoretical roles ascribed to essence by modalists and non-modalists.
Keywords: Essence Nature Identity Definition Modality Essentialism Necessity Explanation Non-modal approaches to essence Modal approaches to essence